2009
DOI: 10.1111/j.1742-4658.2009.07078.x
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+‐induced linker transformation leads to a compact and rigid collagen‐binding domain of Clostridium histolyticum collagenase

Abstract: Clostridium histolyticum collagenase is responsible for extensive tissue destruction in gas gangrene, and its activity is enhanced by calcium ions. The collagen‐binding domain is the minimal segment of the enzyme required for binding to insoluble collagen fibrils and for subsequent collagenolysis. The collagen‐binding domain is joined to another binding module by a conserved 14‐amino‐acid linker. The linker undergoes secondary structural transformation from an α‐helix to a β‐strand and forms a nonprolyl cis‐pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 45 publications
(61 reference statements)
1
29
0
Order By: Relevance
“…This may prolong enzyme activity against insoluble collagen in the extracellular matrix. Calcium-bound holo-s3b was previously shown to be more stable than apo-s3b based on DSC and fluorescence spectroscopy-monitored equilibrium denaturation data (11,12). Similar to the observation in s3b, denaturation pathways obtained using either DSC (Fig.…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…This may prolong enzyme activity against insoluble collagen in the extracellular matrix. Calcium-bound holo-s3b was previously shown to be more stable than apo-s3b based on DSC and fluorescence spectroscopy-monitored equilibrium denaturation data (11,12). Similar to the observation in s3b, denaturation pathways obtained using either DSC (Fig.…”
Section: Resultssupporting
confidence: 70%
“…Meanwhile, the T m value for apo-s3 based on fluorescence data is significantly lower than that determined by DSC (see Table S5 in the supplemental material). The discrepancy in T m was also observed in s3b (12). Analysis of holo-s3 structure using NACCESS (42) demonstrated that Trp925 is solvent inaccessible.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations